THEORETICAL FOUNDATIONS OF THE MOTIVATION OF AN EDUCATIONAL INSTITUTION'S PERSONNEL IN THE MANAGEMENT SYSTEM - Abduraxmanov Obidjon Xabibullayevich (Bright Mind Publishing, 2025)
The innovative development of social and educational spheres worldwide has heightened the demand for management personnel with creative thinking and leadership potential. The 70 Sustainable Development Goals adopted at the UN General Assembly in 2030 emphasize the need for human resource development in education and the creation of professional-oriented training programs. Research efforts globally focus on implementing innovative models for training and retraining management personnel while enhancing the leadership and managerial competencies of educational administrators. Organizations such as the European University Association and the European Network for Quality Assurance in Higher Education are working to develop platforms for leadership assessment through modern information and communication technologies. In this context, the development of management and leadership skills in higher education institutions is crucial for improving education quality and scientific innovation. Key strategies include continuous professional development, personnel assessment, recruitment of creative and competent employees, and the use of digital technologies in staff training. Additionally, psychological support and motivation management play vital roles in increasing employee engagement and institutional success. By fostering a positive work environment, professional growth, and modern teaching methodologies, higher education institutions can ensure long-term sustainability and effectiveness in education management.
Keywords: Motivation, personalization, technology, quality-effectiveness, approach-based learning, management, self-learning, stimulation.